ALDEHYDE EMISSIONS FROM A STATIONARY DIESEL ENGINE OPERATING WITH CASTOR OIL BIODIESEL – DIESEL OIL BLENDS - Zarante, P. B.; da Silva, M. J.; Valente, O. S.; Sodré, J. R. (Revista de Engenharia Térmica, 2010)
The presence of aldehyde in the exhaust gas of a stationary, direct injection, compression ignition engine operating with castor oil biodiesel/diesel oil blends (B5, B10, B20 and B35) is analyzed. The diesel engine was operated with constant speed of 1800 rev/min and load of 37.5 kW. The gas sample was collected directly from the exhaust. Aldehydes were identified and quantified using gas chromatography (GC) with flame ionization detector analyzer (FID). Acetaldehyde presented higher exhaust concentration than formaldehyde for all fuel blends tested. In general, the exhaust aldehyde levels were very low and did not present significant differences between the fuel blends tested.